2011
DOI: 10.1186/2191-0855-1-23
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to electrical stimulation of human immunodeficiency virus type 1 and MAGIC-5 cells

Abstract: To determine the sensitivities to low electrical potential of human immunodeficiency virus type 1 (HIV-1) and its target cells, HIV-1 and MAGIC-5 cells were directly stimulated with a constant direct current potential of 1.0 V (vs. Ag/AgCl). HIV-1 was incubated for 3 h at 37°C on a poly-L-lysine-coated indium-tin oxide electrode, and then stimulated by an electrical potential. MAGIC-5 cells were seeded onto the electrically stimulated HIV-1 and cultured for 3 days at 37°C. HIV-1-infected cells were measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
3
6
0
Order By: Relevance
“…Additionally, we emphasized that the codified number of ions produced from LRD are responsible to reduce the SARS-CoV-2 viral load but not the precipitate produced by metal rods used in the LRD. This data is consistent with previously published data about the effect of electric stimulation on viral infectivity [15,25,26]. The mechanism of how electric stimulation reduces the infectivity of respiratory viruses is still unclear.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Additionally, we emphasized that the codified number of ions produced from LRD are responsible to reduce the SARS-CoV-2 viral load but not the precipitate produced by metal rods used in the LRD. This data is consistent with previously published data about the effect of electric stimulation on viral infectivity [15,25,26]. The mechanism of how electric stimulation reduces the infectivity of respiratory viruses is still unclear.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, stimulation of auricular vagus nerve by electric frequencies reduced the side effects of lung inflammations caused by SARS-CoV-2 [25]. Additionally, patients infected with human immunodeficiency virus type 1 (HIV-1) exposed to low electric potential frequencies showed minimal side effects and reduction of the viral infectivity [16,26]. Interestingly, the previous reports are consistent with our hypothesis about viral infectivity reduction using the codified number of ions produced by LRD.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Treating the coronavirus by an electric stimulus may sound absurd, however literature provides interesting findings and indicates that electric stimulation may be an effective approach to reduce viral burden in COVID-19 patients. Furthermore, the application of electric current is known to improve drug penetration [9] . A short impulse of low voltage current can irreversibly damage the viral membrane.…”
Section: Justification Of Hypothesismentioning
confidence: 99%
“…Several studies [ 17 , 18 , 19 ] indicated that cells, bacteria, and viruses are affected by a pulsed electric current or direct current (DC) with different wavefronts. Kumagai et al [ 20 , 21 ] used a constant DC potential of 1.0 V to stimulate HIV type 1 (HIV-1) and MAGIC-5 cells. Their results indicated that HIV-1LAI and HIV-1KMT infections were inhibited by 90% following 3 min of stimulation; however, the healthy cells were not damaged.…”
Section: Introductionmentioning
confidence: 99%